Position of Polish Agricultural Production Cooperatives on the International and Domestic Market - Matyja, Małgorzata (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2016)
The historical as well as recent experiences show that in some countries and sectors cooperatives play a key role. The agricultural cooperatives are the organizations where farmers pool their resources in certain areas of activity. A fundamental differences between the agricultural cooperatives in develop countries and the CEEC exist. To add insight to the understanding these differences the paper presents some relevant, secondary data. Precisely, the purpose of the article is to investigate the position of Polish agricultural production cooperatives (APCs) on the domestic market and in comparison to cooperatives in developed countries. A main finding is that there is observed a phenomenon of decreasing number of APCs, poorly recognized brands, a relative small turnovers and market shares in comparison to agricultural cooperatives in developed countries.